Effect of preoperative oral carbohydrate combined with postoperative early enteral nutrition on the perioperative rehabilitation of patients with colorectal cancer: a multicenter randomized controlled trial - He, Zeyin; Liu, Yong; Xu, Qiyin; Yang, Xiaobo; Zhou, Dongbing; Zhang, Lili (Frontiers in Nutrition, 2025)
BackgroundPreoperative oral carbohydrates (CHOs) have been widely utilized to improve perioperative outcomes. However, the effect of postoperative early enteral nutrition (EEN) intervention on patients’ postoperative recovery has yet to be validated by prospective outcomes. This study was designed to investigate the effect of preoperative oral CHOs combined with ENN nutrition on postoperative recovery in patients with colorectal cancer (CRC).MethodsA multicenter, prospective, randomized controlled study was conducted on 331 CRC patients who underwent radical resection from March 1, 2022, to March 1, 2023 and were divided into Group A (preoperative oral CHOs combined with postoperative ENN group, n = 110), Group B (preoperative oral CHOs group, n = 110), and Group C (conventional control group, n = 111) according to the method of the randomized numerical table. The general clinical data, inflammatory indices, nutrition-related serum biomarkers, immune function, postoperative intestinal function recovery, complications and hospitalization length of the three groups were statistically analyzed.ResultsThe baseline characteristics were similar among the groups. In the intention-to-treat analysis, the time to first exhaust (p < 0.05) and defecation (p < 0.05) was significantly shorter in group A than in groups B and C. The total protein (TP) level was significantly greater in group A than in groups B and C on the seventh postoperative day (p < 0.05). In addition, the percentage of T-lymphocytes to lymphocytes on the third postoperative day was greater in Group A than in Groups B and C (p < 0.05), and the length of hospitalization was significantly reduced. However, there was no difference in the incidence of postoperative complications.ConclusionPreoperative oral CHOs combined with postoperative EEN improved serum markers related to postoperative nutrition, enhanced the immunity of the body, and promoted early recovery of intestinal function. Preoperative oral CHOs combined with postoperative EEN is conducive to rapid postoperative recovery and reduces the length of hospitalization.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=144616, identifier ChiCTR2100054459.